A Novel Surgical Approach for the Management of Cloacal Exstrophy with a Giant Omphalocele - Smith, Caitlin A.; Avansino, Jeffrey R.; Merguerian, Paul; Lane, Victoria; Levitt, Marc (European Journal of Pediatric Surgery Reports, 2021)
Cloacal exstrophy is a rare malformation that presents as a lower midline abdominal wall defect which affects the gastrointestinal and genitourinary systems. The components of cloacal exstrophy characteristically include omphalocele, exstrophy of perineal structures, and imperforate anus. Most of these patients also have renal anomalies such as pelvic kidney, fused kidneys, or solitary kidneys. This congenital condition can also be associated with spinal issues, such as spinal dysraphism. When combined with spinal defects, it is referred to as the omphalocele, exstrophy, imperforate anus, and spinal defects (OEIS) complex, and is one of the most challenging surgical conditions to manage. Here, we present a unique case of a low-birth-weight patient with OEIS and a liver containing giant omphalocele and the novel surgical technique used to manage her cloacal exstrophy whereby the cecal plate was not separated from the bladder halves, but rather left for an autoaugment, and the ileum was connected to the hindgut.
Keywords: cloacal exstrophy; bladder exstrophy; anorectal malformation